IMMUNE RESPONSES OF TILAPIA OREOCHROMIS NILOTICUSBY WITH THE PROVISION OF XANTHONES EXTRACTED FROM MANGOSTEEN PEEL GARCINIA MANGOSTANA - Mardiana Mardiana; Sutia Budi (OCTOPUS : JURNAL ILMU PERIKANAN, 2016)
This study aims to t analyze the influence of the provision of extract the rind Mangosteen of xantone on increased response immun of Tilapia fish. The study is done in vitro and in vivo, The research using random design complete (RAL) with the observation parameters of phagocytosis test activity and survival rate. This research intended to evaluate the response immun non-spesifik on Tilapia (O. niloticus) extracted  from mangosteen peel. The results of the analysis variety of ANOVA shows that nila fish given extract xanthones, had have real impact on survival nila fish (P0,05).  Test results said W-tukey shows that survival highest nila fish is in the provision of xanthones 2,10 ppm / the tail (Treatment C) and are no different by the provision of xanthones by 2.15 ppm / the tail (Treatment D) but different to the provision of xanthones 2.5 ppm/the tail (Treatment B) and control (Treatment  A). The results of the analysis variety of ANOVA shows that activity of phagocytosis also had have real impact (P 0.05) between any treatment, test results said W-tukey treatment control different to treatment B, C and  D but also between treatment B and treatment D not different.